Microenvironmental Control of High-Speed Interstitial T Cell Migration in the Lymph Node - Katakai, Tomoya; Kinashi, Tatsuo (Frontiers in Immunology, 2016)
T cells are highly concentrated in the lymph node paracortex, which serves an important role in triggering adoptive immune responses. Live imaging using two-photon laser scanning microscopy revealed vigorous and non-directional T cell migration within this area at average velocity of more than 10 µm/min. Active interstitial T cell movement is considered to be crucial for scanning large numbers of dendritic cells (DCs) to find rare cognate antigens. However, the mechanism by which T cells achieve such high-speed movement in a densely packed, dynamic tissue environment is not fully understood. Several new findings suggest that fibroblastic reticular cells (FRCs) and DCs control T cell movement in a multilateral manner. Chemokines and lysophosphatidic acid produced by FRCs cooperatively promote the migration, while DCs facilitate LFA-1–dependent motility via expression of ICAM-1. Furthermore, the highly dense and confined microenvironment likely plays a key role in anchorage-independent motility. We propose that T cells dynamically switch between two motility modes; anchorage-dependent and -independent manners. Unique tissue microenvironment as well as characteristic migration modality of T cells cooperatively generate high-speed interstitial movement in the lymph node.